A laser irradiation synthesis of strongly-coupled VOx-reduced graphene oxide composites as enhanced performance supercapacitor electrodes. (September 2017) - Zhang, Lin-Fei; Tang, Jun; Liu, Shi-Yuan; Peng, Ou-Wen; Shi, Run; Chandrashekar, Bananakere Nanjegowda; Li, Yan; Li, Xin; Li, Xiang-Nan; Xu, Bao-Min; Cheng, Chun
Abstract: A unique technique is present to synthesize three dimensional hierarchical vanadium oxides/reduced graphene oxide composites (denoted as 3D VOx /rGO composites) by laser irradiation over the mixture of V2 O5 nanobelts and GO nanosheets. Electron microscopy and X-ray photoelectron spectroscopy (XPS) examinations reveal that polydisperse V2 O5 /VO2 heterostructured nanoparticles form strong coupling with rGO. As a result, a specific capacitance of 252 F g −1 is achieved for 3D VOx /rGO composites when used as supercapacitor electrodes, and the capacitance can retain 92% of the initial specific capacitance even after 10000 cycles at a current density of 100 A g −1 . The improvement of supercapacitor performance is achieved by significantly increase on specific surface area of 3D VOx /rGO composites, which favors the easy access of the electrolyte and provides large electroactive surface, and strong VOC bond between VOx nanoparticles and rGO, which benefits the effective charge transfer. We believe that the facile laser irradiation approach represents a major step not only for the simple and efficient fabrication of high performance electrodes but also in the practical application of laser processing to synthesize other functional hierarchical nanocomposites. Graphical abstract: Highlights: This work maybe the first report to apply laser irradiation on the efficient preparation of VOx /rGO nanocomposites. This work highlights the advantages of the usage of laser irradiation for the VOx /rGO composites preparation. This work indicates the laser irradiation process can be emerging as a robust, cost-less and environmental-friendly strategy.